Staphylococcus aureus overinfection in atopic dermatitis - Ricci, Giampaolo; Dondi, Arianna; Patrizi, Annalisa (Journal of Pediatric Infectious Diseases, 2008)
The skin of patients affected by atopic dermatitis (AD) is extremely susceptible to colonization by Staphylococcus aureus, which plays an important role in AD exacerbations and is correlated with AD extent and severity. The mechanisms by which the bacterium colonizes and infects the skin of patients with AD can be summarized by three different and subsequent steps: 1) a defective skin barrier, on which 2) S. aureus is able to adhere and proliferate thanks to 3) the defective immune response of the skin. Several S. aureus strains can secrete enterotoxins, which can act as superantigens thus contributing to disease severity by inducing a polyclonal T-cell activation and the release of proinflammatory cytokines such as TNFα, IL-1β, IL-2. The production of immunoglobulin E antibodies against staphylococcal exotoxins has also been demonstrated, and the staphylococcal wall protein A has been suggested to act as a “superallergen”. Therapeutical actions against S. aureus skin overinfection include both pharmacological (antimicrobial and/or anti-inflammatory therapy and the newer topical calcineurin inhibitors) and nonpharmacological treatments (silk fabric textiles), and are aimed at minimizing skin colonization in order to reduce clinical exacerbations and AD severity.
Keywords: Childhood eczema; atopic dermatitis; S. aureus; superantigens; superallergens